{2- (2-Carbamothiolylhydrazin-1-ylidene-kappa N-2(1),S)methyl -6-hydroxyphenolato-kappa O-1}(triphenylphosphine-kappa P)nickel(II) chloride - Tan, Kong Wai; Ng, S.W.; Shawish, H.B.; Maah, Mohd Jamil (International Union of Crystallography, 2010)
The deprotonated Schiff base ligand in the title compound, [Ni(C8H8N3O2S)(C18H15P)]Cl, functions as an N,O,S-chelating anion to the phosphine-coordinated Ni atom, which exists in a distorted square-planar geometry. The hydroxy group forms an intramolecular O-H center dot center dot center dot O hydrogen bond. The two amino groups of the cation are hydrogen-bond donors to the chloride anion; the hydrogen bonds generate a chain structure running along the b axis.